The Effect Of Spcial Exercies On Legs Explosive Power and 100m and 200m Youth Runners' achivment - Mtab, Sohir (Journal of Physical Education, 2017)
The aim of the reseach is designing exercises for 100m and 200m youth runners.The reseacher designed the exercises accoridng to interval training with high intensity. Theprogram inlcuede 24 training sessions applied on 12 runners from the national center forgifted athletes in atheltics aged 18 – 19 years old.the subjects were tests using dynafoot forlegs explosive power, 100m and 200m achivment test. the results showed developemnt in 100m achviment more than in 200m. in addidtion to that explosive power training has a greateffect in imporving physical abilities and the working muslcs in both perfraomnce andphysical ability.